RANCANG BANGUN APLIKASI DAN IMPLEMENTASI METODE FAM UNTUK SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN TINGKAT KEPUASAN MAHASISWA UNPAM TERHADAP PEMBELAJARAN TATAP MUKA TERBATAS - Muhammad Qifli Hidayatullah (Jurnal Penelitian Ilmu komputer, 2023)
An application is designed and built to investigate how the impact of the Covid-19 pandemic on tertiary institutions can affect the services provided to students when the implementation of the limited face-to-face learning method has an impact on the level of student satisfaction.decision support to assist decision making based on the level of satisfaction with academic and non-academic services. The application built is a desktop-based Java application using JavaFx as the interface. This application uses the fuzzy associative memory method as a decision support method that maps between one fuzzy set and another fuzzy set. Design and implementation are designed to be as easy as possible to facilitate the visualization of the methods used to make it easier to understand. The application's results are the number of decision results based on the categories given in the form of Unsatisfactory, Fairly Satisfying, and Very Satisfying. The results obtained from entering the fuzzy set into other fuzzy sets provide optimal results in determining the level of student satisfaction in implementing this limited face-to-face learning. These results can be used as material for comparison in future service development and for purposes other than academic interests.